Micro-Determinants of Informal Employment in the Middle East and North Africa Region - Angel-Urdinola, Diego F. (World Bank, Washington, DC, 2017)
This note assesses the main micro?determinants of informal employment in the Middle East and North Africa (MENA) region from a human development stand point. It's main purpose is to quantify the patterns of labor informality (defined as the share of all employment with no access to social security) according to age, gender, education level, employment sector, profession, marital status, employment status, and geographic area in a selected group of countries in the region. Results indicate that the size of the public sector and the size of the agriculture sector are perhaps the main correlates of informality in the region. Countries where agricultural employment still constitutes a large share of overall employment (such as Morocco and Yemen) are associated with higher levels of overall informality. On the contrary, countries with larger public sectors and more urbanized such as Egypt, Syria, and Lebanon, display lower levels of overall informality. The existence of a large public sector, still associated with generous benefits and better employment quality, creates an important segmentation between public and private employment in many MENA countries. Informality rates are very high among youth between ages fifteen and twenty-four. After age twenty-four, informality decreases rapidly until individuals reach prime working age (forty to forty?five years). This rapid decrease in informality rates goes hand in hand with a rapid increase in public sector employment, suggesting that informal workers enter into public sector jobs as they move from youth into adulthood. Results also indicate that the average worker in the informal sector is disadvantaged versus the average worker in the formal sector, as they are uncovered against social risks and are generally employed in low-productivity/low pay jobs.